Ethische Perspektiven und Aufgaben einer europäischen Arbeitsmarktpolitik für die Zukunft - Strohm, Theodor (Zeitschrift für evangelische Ethik, 1994)
Besides the economical criteria of convergence, which have been precisely laid down in the EC-treaties, especially in the treaties of Maastricht, the integration of labour markets is an explicit aim of the European Union. Considering that approx. 19 million employees within the EC are not gainfully employed, a common and well-aimed labour market policy seems to be one of the major responsibilities of European economical and social policy. The instruments of job creation and preservation in Germany are being compared with the aims of the EC-comission, also experiences of other countries are being involved. The Christian Churches in Europe are committed to get involved in tackling unemployment and its human-destructing effects. The Social Chamber of the EKD has made continuous proposals. At present, it is working on continuing its previous memorandums on unemployment. With this, also the memorandum ))Responsibility for a Social Europe« (1992) is being continued and put into concrete terms.